Sex-workers in Bangladesh, livelihood, at what price? - Tahmina, Q. A.; Moral, Shishir; Society for Environment and Human Development (Dhaka, Bangladesh) (Dhaka : Society for Environment and Human Development, 2004)
Contributed articles.
Includes bibliographical references (pages [273]-276).
ESS
Keywords: Prostitutes -- Bangladesh -- Social conditions